Aplikasi E-Commerce Ikan Teri dengan Metode Waterfall dan Integrasi Pembayaran Midtrans - Rahman, Muhammad Zaldi; Alda, Muhamad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The development of digital technology has encouraged many small and medium enterprises (SMEs) to shift to e-commerce platforms to expand their market reach. Abdul Rahman's business, which deals with the sale of anchovies, faces challenges in marketing and effective payment systems. Therefore, the development of an e-commerce application is needed to increase sales efficiency and provide convenience in transactions. This research aims to design and develop an e-commerce application for Abdul Rahman's business using the Waterfall software development method. This method was chosen because of its systematic and structured process, making it suitable for the needs of a small-scale business. The development stages include requirements analysis, system design, coding, testing, and maintenance. Additionally, this application is integrated with Midtrans, a payment gateway that allows customers to make payments through various methods such as bank transfers, credit cards, and digital wallets, simplifying the online transaction process. The final result of this research is an e-commerce application that can be used to market anchovy products more broadly and provide convenience in purchasing and secure, fast payment processes. System testing shows that the application functions as expected and can enhance the user experience in online shopping.